ETHNICITY IN THE MATRIX OF PEACE AND RECONCILIATION IN NIGERIA - Erhagbe, Eddy (European Scientific Journal, ESJ, 2012)
Some come features of the post-colonial states in Africa include their multi-ethnic composition, disagreements and conflicts among the groups and sometimes armed conflicts. Unfortunately for Nigeria it fits into the above hue. Considering the unending antagonism among the ethnic groups in Nigeria, the subject of how best to manage their relationships remains topical. Among other things, this work examines the nature of the ethnicity phenomenon in Nigeria, how it has affected and negated reconciliation among the groups and re-emphasizes some steps that must be adopted to continuously address the problem.